A Prediction Method of Wear for Volute Casing of a Centrifugal Slurry Pump. (18th December 2020) - Shi, Baocheng; Pan, Jianpeng; Wu, Lijuan; Zhang, Xingkai; Qiu, Yijie; Zhang, Yindi
Abstract : Volute wall wear situations directly affect a long time safe operation for the centrifugal slurry pump unit and the whole system. In the present study, internal flow field is numerically investigated in a solid-liquid centrifugal pump, and the volute wall wear caused by the solid-liquid two-phase flow is predicted with wear equation. A systematic analysis on the wear mechanism of the centrifugal pump volute wall is carried out deeply, including the volute wall wear region, wear rate, and the relationship among inlet flow rate, particle concentration, and particle size. The predicted high erosion intensity area shows good agreement with the experimental erosion area, and the predicted and experimental areas are both located at the volute angle of 180° and near tongue. Therefore, the wear equation put forward in the present study is effective for estimating the erosion intensity and predicting the erosion area around the volute casing of a centrifugal pump.